Analysis of the patient occupancy rate (BOR), operational cost budget and activity ratio on financial performance based on income capability of PNBP covering operational cost of public service agency (BLU) of DKI Jakarta provincial hospital. - Istiqomah Dwi Putri; Achmad Fauzi (Jurnal Ilmiah Wahana Akuntansi, 2017)
The purpose of this research is to know the influence of activity, operational cost budgeting, and bed occupancy rate on financial performance based on ability of (PNBP) revenue to cover operating cost public service agency hospital. This study aims to determine the effect of patient occupancy rate (BOR), operational budget and activities of financial performance is based on the ability of non-tax revenue to cover operating costs hospital public service agencies in the province of Jakarta period 2011-2015. Descriptive analysis showed that: (a) the value of BOR at Hospital studied quite well with a range of over 60%, (b) the absorption of operational budget is considered quite efficient because it has a small difference from the budget, (c) the ratio of activity with time measurement average receivables collectible on average figures, The results of this study indicate that patient occupancy rate (BOR), and Budget operasionalof positive and significant impact on the financial performance Hospital General Services Agency activity while variable does not affect the financial performance of the Hospital